Easily misdiagnosed intramuscular hemangioma: a case report and literature review - Lei, Rong; Tian, Linqiang (Frontiers in Surgery, 2025)
Intramuscular hemangioma is a benign tumor, usually occurring in the lower limbs. We report a rare case of intramuscular hemangioma that occurred in the gluteus medius muscle and was misdiagnosed as an injury to the gluteus medius muscle with bleeding. A 36 year old male presented with left hip pain after a clear history of trauma. He was diagnosed with damage to the gluteus medius muscle and bleeding, and received treatment, but the pain did not improve significantly. Magnetic resonance imaging(MRI) shows the formation of hematoma in the gluteus medius muscle.The patient underwent MRI enhancement and was ultimately diagnosed with a gluteal muscle hemangioma.Patients with intramuscular hemangioma usually do not have specific symptoms and have a clear history of trauma for this patient.Therefore, this type of tumor is often misdiagnosed. When the treatment effect is not ideal, the diagnosis should be re evaluated in a timely manner.